Sirolimus Monotherapy for Thrombocytopenia in Primary Antiphospholipid Syndrome: A Pilot Study From a Tertiary Referral Center - Xie, Wenhui; Ji, Lanlan; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background: Thrombocytopenia (TP) is considered as a warning sign of high-risk antiphospholipid syndrome (APS) and sometimes a paradoxical sign of anti-thrombosis treatment. Currently there is an extreme paucity of effective and safe drugs for long-term management of TP in primary APS patients, therefore we explored the efficacy and safety of sirolimus monotherapy. Methods. In this real-world study, we included 7 consecutive patients with primary APS who received sirolimus monotherapy for TP. Oral sirolimus was initiated at a dose of 1-2 mg once daily and then adjusted primarily based on clinical efficacy and tolerance, with consideration of sirolimus trough concentration of 15 ng/ml. Results. Of included patients, the median age was 58 years with median disease course of 1.5 years and 4 patients were treatment-naïve. All patients completed 6 months of sirolimus therapy with median follow-up of 6 months (range: 6-15). All patients received sirolimus monotherapy for TP during entire follow-up, without adding any additional agents. Overall, platelet count exhibited substantially increasing trend after sirolimus administration during the first six months (p<0.001) and being stable later. Specifically, median platelet count was significantly increased from 59×109/L before sirolimus to 90×109/L at month 1 (p=0.028), 131×109/L at 3 months (p=0.028) and 178×109/L at 6 months (P=0.018). Overall and complete response were respectively achieved in 6 (85.7%) and 5 (71.4%) patients at month 6. Importantly, overall response was achieved in all 4 treatment-naïve patients. Additionally, there was different extents of decline in the titers of antiphospholipid antibodies after sirolimus treatment. Regrading safety, only one patient experienced elevated cholesterol level with recovery after atorvastatin treatment. Conclusion. Sirolimus monotherapy confers good efficacy and tolerance for TP in primary APS patients, and therefore may be considered as a first-line therapy.